Proceedings of the 2015 Annual Conference on Genetic and Evolutionary Computation 2015
DOI: 10.1145/2739480.2754694
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Objective Vector-Based Genetic Programming Using Human-Derived Primitives

Abstract: Traditional genetic programming only supports the use of arithmetic and logical operators on scalar features. The GTMOEP (Georgia Tech Multiple Objective Evolutionary Programming) framework builds upon this by also handling feature vectors, allowing the use of signal processing and machine learning functions as primitives, in addition to the more conventional operators. GTMOEP is a novel method for automated, data-driven algorithm creation, capable of outperforming human derived solutions.As an example, GTMOEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…In auto-sklearn, [5] imposed a short and fixed pipeline structure of a data preprocessor, a feature preprocessor, and a model. In another GPbased AutoML system, [22] allowed the GP algorithm to design arbitrarily-shaped pipelines and found that complex pipelines with several preprocessors and models were useful for signal processing problems. Thus, it may be vital to allow AutoML systems to design arbitrarily-shaped pipelines if they are to achieve human-level competitiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In auto-sklearn, [5] imposed a short and fixed pipeline structure of a data preprocessor, a feature preprocessor, and a model. In another GPbased AutoML system, [22] allowed the GP algorithm to design arbitrarily-shaped pipelines and found that complex pipelines with several preprocessors and models were useful for signal processing problems. Thus, it may be vital to allow AutoML systems to design arbitrarily-shaped pipelines if they are to achieve human-level competitiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond using GP to perform the machine learning itself, recent work has shown that GP can also be harnessed to optimize a sequence of existing data analysis and machine learning operations on a dataset to maximize the predictive performance of the final machine learning model [30,35]. For example, TPOT 4 is an early prototype that uses GP to optimize a sequence of scikit-learn operations for both classification and regression problems [25][26][27], and has been shown to work quite well across a broad range of application domains ranging from epidemiological studies to image classification to time series prediction [23].…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…3. Construção automática de pipelines de aprendizagem de máquina com algoritmos genéticos [Zutty et al 2015] demonstraram que a otimização com algoritmos genéticos pode superar os seres humanos na busca de um pipeline de aprendizagem de máquina 2 que melhor se encaixa em uma tarefa de aprendizagem supervisionada. Nesse sentido, [Olson et al 2016] propuseram um método para construção automática de pipelines chamado de Treebased Pipeline Optimization Tool (TPOT), no qual a intençãoé criar, inicialmente, uma população inteira de pipelines aleatórios e evoluí-los com operadores de mutações e cruzamentos ao longo de gerações.…”
Section: Trabalhos Relacionadosunclassified